2018
DOI: 10.1101/483818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring differentially expressed key genes related to development of follicle by RNA-seq in Peking ducks (Anas Platyrhynchos)

Abstract: Duck follicle enter different reproductive phases throughout life, and follicle gene expression patterns differ according to these phases. In particular, differentially expressed genes and related to development of follicle (mRNAs) play an important role to explore the key genes in this process; however, the expression profiles of these genes remain unclear. In this study, transcriptome sequencing was used to investigate the expression levels of duck ovarian genes, and comparative transcriptional analysis was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The differences between these groups might be due to the number of follicles present in the LP and HP ducks which are closely related to the secretion of important reproductive hormones (LH and FSH) as reported by a study that the higher the number of follicles, the greater the number of egg produced in laying geese ( Yang et al, 2019 ). Moreover, a transcriptome study in Peking ducks revealed that variation in egg-laying might be due to the differences in the development of ovaries and follicles which may be closely associated with the ovarian steroid synthesis pathway ( Ren et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between these groups might be due to the number of follicles present in the LP and HP ducks which are closely related to the secretion of important reproductive hormones (LH and FSH) as reported by a study that the higher the number of follicles, the greater the number of egg produced in laying geese ( Yang et al, 2019 ). Moreover, a transcriptome study in Peking ducks revealed that variation in egg-laying might be due to the differences in the development of ovaries and follicles which may be closely associated with the ovarian steroid synthesis pathway ( Ren et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sex in birds and mammals is governed by sex chromosomes [1], and sex determination genes on sex chromosomes initiate sex differentiation and regulate the differentiation of gonads into ovaries or testes [2]. A host of critical gonadal differentiation genes have been detected [3,4]. However, screening for novel regulators of male and female embryos is highly necessary to enhance our understanding of gonadal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In domestic ducks, several candidate genes involved in the development of plumulaceous feather and flight feather structures were obtained by RNA-Seq [21]. Research in Peking ducks has revealed that a key regulator of duck follicle development in the laying period [3]. In addition, RNA-Seq is also widely used to explore the mechanism of sex differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been a push toward applying transcriptome methods in ornithological studies over the recent years (Jax, Wink, & Kraus, 2018), little is known about the age‐specific gene expression in birds. Age‐specific gene expression in follicles of Peking ducks ( Anas platyrhynchos ) indicated no clear pattern regarding expression levels in relation to age (Ren et al., 2019), while in great tits ( Parus major ), age classes were not associated with differential gene expression levels in blood and liver (Watson, Videvall, Andersson, & Isaksson, 2017). Conversely, in the present study, we found that more than 90% of the differentially expressed genes (including also transcripts that were not related to cancer) were downregulated in older birds.…”
Section: Discussionmentioning
confidence: 99%